Psychometric Properties of the COVID-19 Protective Motivation Scale in Peruvians During the Health Emergency - Bruno Cornejo; Brayan Vela; Lindsey W. Vilca; María Vallejos; Salomón Huancahuire-Vega (SAGE Publishing, 2021)
Objective: The COVID-19 protective motivation scale (EMP-COVID-19) has been developed for the assessment of protective motivation. This study aims to examine the psychometric properties of the EMP-COVID-19 for its application in the Peruvian community. Methods: This is an observational, cross-sectional, instrumental design study, 483 adults (≥18 years) participated in the study, in 2 samples of 81 and 402 participants from the different macro-regions of Peru through an online survey using non-probabilistic sampling. Content validation was performed through expert judgment. Exploratory factor analysis (EFA) to evaluate the factor model of the EMP-COVID-19 was performed with the first sample. The confirmatory factor analysis (CFA) to verify the goodness of fit of the analysis found in the EFA was performed with the second sample. The examination of convergent and discriminant validity included peer evaluations of each EMP-COVID-19 dimension. Finally, the reliability of the instrument was evaluated using Cronbach's Alpha coefficient. Results: The 3-factor related model presents better fit indices (CFI = 0.99; TLI = 0.99; RMSEA = 0.077 [90% CI 0.069-0.085]) versus a unidimensional model (CFI = 0.91; TLI = 0.90; RMSEA = 0.206 [90% CI 0.199-0.213]). The scale present convergent and discriminant validity in all the dimensions Threat Appraisal (AVE = .57), Coping Appraisal (AVE = .81), and Response Costs (AVE = .67). The Coping Appraisal (α = .97; ω = .97), Threat Appraisal (α = .88; ω = .74), and Response Costs (α = .80; ω = .76) dimensions were also found to have adequate reliability indices. Conclusions: The EMP-COVID-19 scale demonstrated adequate reliability and validity based on internal structure in the study sample.